2015
DOI: 10.1155/2015/309784
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent Syncope Associated with Lung Cancer

Abstract: Syncope is an important problem in clinical practice with many possible causes that might be misdiagnosed. We present an unusual case of syncope, which has a normal chest X-ray. Exercise EKG and coronary angioplasty results confirmed the existence of serious coronary heart disease. The patient was treated with coronary stent transplantation. However, scope occurred again and the elevated tumor makers cytokeratin-19-fragment and neuron-specific enolase revealed the bronchogenic carcinoma, which was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…7 Recurrent syncope can be associated with lung cancer and can present in unusual and cryptic ways including with normal chest radiograph and no respiratory symptoms. 8 Recurrent syncope without a clear cause should also alert the clinician to consider a subclinical presentation of lung cancer. In one case, chest radiography did not reveal any obvious mass until a subsequent chest CT prompted by abnormal labs showed a left mediastinal tumor compressing a branch of the vagal nerve leading to neutrally mediated syncope.…”
Section: Discussionmentioning
confidence: 99%
“…7 Recurrent syncope can be associated with lung cancer and can present in unusual and cryptic ways including with normal chest radiograph and no respiratory symptoms. 8 Recurrent syncope without a clear cause should also alert the clinician to consider a subclinical presentation of lung cancer. In one case, chest radiography did not reveal any obvious mass until a subsequent chest CT prompted by abnormal labs showed a left mediastinal tumor compressing a branch of the vagal nerve leading to neutrally mediated syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Using PubMed, a literature search was performed, and only 8 previously reported cases of SCLC with recurrent syncope were identified (Table I) (310). A total of 9 cases are included in the review, including the present case, comprising a total of 8 men and 1 woman, with a mean age of 62.33±2.12 years.…”
Section: Discussionmentioning
confidence: 99%
“…Syncope is commonly attributed to cardiogenic or cerebral factors when considering differential diagnosis. It has been reported that episodic syncope is rarely caused by small-cell lung cancer (SCLC) (3), and clinicians should bear this possibility in mind, as it may be associated with life-threatening events. However, the mechanism underlying the occurrence of this type of syncope has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the article titled “Recurrent Syncope Associated with Lung Cancer” [1], an acknowledgement should be added.…”
mentioning
confidence: 99%